Answer:
![\large \boxed{\sf \ \ 6 \ and \ 11 \ \ }](https://img.qammunity.org/2021/formulas/mathematics/college/i3a041xfw9y6jxw72mc8ww2y8y6cytlr8c.png)
Explanation:
Hello,
Let's note a and b the two numbers.
a = b - 5
![a^2+b^2=157](https://img.qammunity.org/2021/formulas/mathematics/college/gr50uzwzf3g55vij53qm09p2w6788umcy9.png)
We replace a in the second equation and we solve it
![(b-5)^2+b^2=157 \\ \\ \text{*** develop the expression ***} \\ \\b^2-10b+25+b^2=157 \\ \\ \text{*** subtract 157 from both sides ***} \\ \\2b^2-10b+25-157=2b^2-10b-132=0 \\ \\ \text{*** divide by 2 both sides ***} \\ \\b^2-5b-66=0](https://img.qammunity.org/2021/formulas/mathematics/college/6h1dk678he7ykni1p980ul884wn4w5y6k4.png)
It means that the sum of the two roots is 5 and the product is -66.
because
![(x-\alpha )(x-\beta )=x^2-(\alpha +\beta )x+\alpha \beta \\ \\ \text{ where } \alpha \text{ and } \beta \text{ are the roots }](https://img.qammunity.org/2021/formulas/mathematics/college/6klvsrbo01x2qr7114okfn5fbvvaaw9od8.png)
And we can notice that 66 = 6 * 11 and 11 - 6 = 5
So let's factorise it !
![b^2-5b-66=0 \\ \\b^2+6b-11b-66=0 \\ \\b(b+6)-11(b+6)=0 \\ \\(b-11)(b+6) =0 \\ \\ b=11 \ or \ b=-6](https://img.qammunity.org/2021/formulas/mathematics/college/ybw9kkhp2aowzg5djtzyo3gq3xctf7zivn.png)
It means that the solutions are
(6,11) and (-6,-11)
I guess we are after positive numbers though.
Hope this helps.
Do not hesitate if you need further explanation.
Thank you